Analysis of the relationship between axial length, optic disc morphology, and regional variations in retinal vessel density in young adults with healthy eyes - Chen, Yanhui; Rong, Hua; Liu, Yuling; Gao, Huijuan; Sun, Ziwen; Dang, Weiyu; Lu, Kunpeng; Mi, Baoyue; Li, Jing; Wei, Ruihua (Frontiers in Medicine, 2024)
Purpose: To investigate the relationship between optic disc morphology, axial length, and regional distribution of retinal vessels in healthy eyes of young adults. Methods: Nine-hundred-two healthy eyes were enrolled in this university-based, cross-sectional study.Spectral-domain optical coherence tomography angiography measured the parapapillary retinal vessel density. We automate the process of calculating optic disc tilt and rotation by using Python software, which can save a lot of time and effort compared to manual calculations. Relationships between optic disc rotation, optic disc tilt, parapapillary vessel density, and other ocular parameters were analyzed using regression models. Results: During axial length, optic disc morphology became more tilted and rotated inferiorly. The superficial vessel density (SVD) and radial peripapillary capillaries density (RPCD) decreased gradually in all regions except for the temporal quadrant. Increased temporal SVD (OR [95% CI] =1.081 [1.039, 1.124], P < 0.001), reduced nasal SVD, (OR [95% CI] = 0.898 [0.861, 0.937], P < 0.01) and short relative lens position (OR [95% CI] = 0.126 [0.032, 0.495], P = 0.003) were significantly associated with the presence of tilted disc. Inferiorly rotated of the optic disc was associated with decreased superior deep vessel density (DVD) and increased inferior DVD and temporal DVD after adjusting the sex and axial length. Conclusion: The tilted and rotated discs were associated with the distribution of SVD and DVD, respectively. We should fully consider the influence of optic disc morphology on parapapillary vessel density in eyes with myopia.